Messing up translation from the start: How AtaT inhibits translation initiation in E. coli. Issue 3 (4th March 2018) - Van Melderen, Laurence; Jurenas, Dukas; Garcia-Pino, Abel
ABSTRACT: Toxin-antitoxin systems (TA) are widespread in bacteria and archea. They are commonly found in chromosomes and mobile genetic elements. These systems move from different genomic locations and bacterial hosts through horizontal gene transfer, using mobile elements as vehicles. Their potential roles in bacterial physiology are still a matter of debate in the field. The mechanisms of action of different toxin families have been deciphered at the molecular level. Intriguingly, the vast majority of these toxins target protein synthesis. They use a variety of molecular mechanisms and inhibit nearly every step of the translation process. Recently, we have identified a novel toxin, AtaT, presenting acetyltransferase activity. 1 Our work uncovered the molecular activity of AtaT: it specifically acetylates the methionine moiety on the initiator Met-tRNAfMet. This modification drastically impairs recognition by initiation factor 2 (IF2), thereby inhibiting the initiation step of translation.